Preparation of flexible PLA films using novel plasticizers - Ali, Fathilah; Upadhyay, Arun Kumar (2014)

(untitled)
Most of research attention is focused on the replacement of petro-based commodity plastics by biodegradable polymer with competitive mechanical properties. Poly(lactic acid) (PLA) is produced from renewable resources and is readily biodegradable. Due to the brittleness of PLA, it has limited usage in the packaging and structural applications which require flexibility. In this study, novel type plasticized PLA films were prepared. The plasticized PLA was mixed with 3-amino-1,2,4-triazole (ATA) in an internal mixer. The mechanical studies revealed the elongation is increased significantly with small amount of ATA accompanied with whitening and the modulus is decreased. Melt rheological analysis showed that viscosity increased with content of ATA.